Infectious Agents and Inflammation: The Role of Microbiota in Autoimmune Arthritis - Picchianti-Diamanti, Andrea; Rosado, Maria M.; D’Amelio, Raffaele (Frontiers in Microbiology, 2018)
In higher vertebrates, mucosal sites at the border between the internal and external environments, directly interact with bacteria, viruses, and fungi. Through co-evolution, hosts developed mechanisms of tolerance or ignorance toward some infectious agents, because hosts established “gain of function” interactions with symbiotic bacteria. Indeed, some bacteria assist hosts in different functions, among which are digestion of complex carbohydrates, and absorption and supply of vitamins. There is no doubt that microbiota modulate innate and acquired immune responses starting at birth. However, variations in quality and quantity of bacterial species interfere with the equilibrium between inflammation and tolerance. In fact, correlations between gut bacteria composition and the severity of inflammation were first described for inflammatory bowel diseases and later extended to other pathologies. The genetic background, environmental factors (e.g., stress or smoking), and diet can induce strong changes in the resident bacteria which can expose the intestinal epithelium to a variety of different metabolites, many of which have unknown functions and consequences. In addition, alterations in gut permeability may allow pathogens entry, thereby triggering infection and/or chronic inflammation. In this context, a local event occurring at a mucosal site may be the triggering cause of an autoimmune reaction that eventually involves distant sites or organs. Recently, several studies attributed a pathogenic role to altered oral microbiota in rheumatoid arthritis (RA) and to gut dysbiosis in spondyloarthritis (SpA). There is also growing evidence that different drugs, such as antibiotics and immunosuppressants, can influence and be influenced by the diversity and composition of microbiota in RA and SpA patients. Hence, in complex disorders such RA and SpA, not only the genetic background, gender, and immunologic context of the individual are relevant, but also the history of infections and the structure of the microbial community at mucosal sites should be considered. Here the role of the microbiota and infections in the initiation and progression of chronic arthritis is discussed, as well as how these factors can influence a patient’s response to synthetic and biologic immunosuppressive therapy.